PENGGERAKAN PELAKU DAKWAH PADA HIMPUNAN DA’I DAN MUBALLIGH KOTA BUKITTINGGI - Vina Melyani; sarwan sarwan; Yummil Yummil; Fitriani Ayu Lestari (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Many difficulties in moving organizations that only work on the basis of sincerity. The purpose of this study is to reveal the efforts of Himpunan Da’i dan Muballigh in moving the da'wah in Bukit Tinggi City, which consists of providing motivation, guidance, coordination, and communication from the leader to the members. This study uses a qualitative method. First, the motivation is generally abstract, even though there is material giving which is of little value and if there is something of economic value not all members get it. Second, the guidance given by the Da'wah leaders to members is guidance that fosters sincerity and togetherness not because of demanding obligations. Third, the relationship between the Da'wah leaders and members has not been well established, because there are members who have doubts when asked as members / management, and some who do not know about the development of the organization. Fourth, leadership communication with members is more mobile.